DINAMIKA PERKEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI INDONESIA DARI MASA KE MASA - Munir, Misbahul; Irhas Sabililhaq; Noni Yuanda; Lia Dwi Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of the Islamic religious education curriculum in Indonesia began in 1947, 1952, 1975, and 1994. During the reformation period, it began with the 2001 KBK curriculum, the 2006 KTSP curriculum, the 2013 curriculum, and the Merdeka curriculum. The purpose of this study is to analyze changes in the education curriculum. The method used in this study is library research. In its development process, the curriculum is dynamic and adaptive to the development of the times and technology. However, in its implementation, the curriculum is still not optimal due to the lack of facilities and infrastructure and the uneven distribution of education throughout all regions in Indonesia.